Brand consciousness among women for purchasing makeup products - Singh Chauhan, Jitendra (International Journal of Psychosocial Rehabilitation, 2019)
Style-conscious women account for over two-thirds of total spending on women’s apparel, accessories, and beauty. The style-conscious woman spends three times more than the average woman. Price is not her most important consideration. Her favourite brands cover all price points, and she is willing to pay more to get exactly what she wants. A narrow band of style-conscious women account for the vast majority of US luxury sales. Retail therapy, for long, has been a space that women have occupied. And they aren’t ready to move out, even as gender differences seem to blur in this day and age. Women still want their womanly shopping time, once a week or, in some cases, every other day. These women spend disproportionately on luxury—a testament to the growing luxury brands space—and look for any reason to shop.